Sponge organic matter recycling: Reduced detritus production under extreme environmental conditions. (May 2023) - Maggioni, Federica; Bell, James J.; Pujo-Pay, Mireille; Shaffer, Megan; Cerrano, Carlo; Lemonnier, Hugues; Letourneur, Yves; Rodolfo-Metalpa, Riccardo
Abstract: Sponges are a key component of coral reef ecosystems and play an important role in carbon and nutrient cycles. Many sponges are known to consume dissolved organic carbon and transform this into detritus, which moves through detrital food chains and eventually to higher trophic levels via what is known as the sponge loop. Despite the importance of this loop, little is known about how these cycles will be impacted by future environmental conditions. During two years (2018 and 2020), we measured the organic carbon, nutrient recycling, and photosynthetic activity of the massive HMA, photosymbiotic sponge Rhabdastrella globostellata at the natural laboratory of Bouraké in New Caledonia, where the physical and chemical composition of seawater regularly change according to the tide. We found that while sponges experienced acidification and low dissolved oxygen at low tide in both sampling years, a change in organic carbon recycling whereby sponges stopped producing detritus (i.e., the sponge loop) was only found when sponges also experienced higher temperature in 2020. Our findings provide new insights into how important trophic pathways may be affected by changing ocean conditions. Graphical abstract: Unlabelled Image Highlights: Sponge metabolism was measured at the natural laboratory of Bouraké where sponges are naturally exposed to extreme conditions associated with tidal phase. The photosymbiotic HMA sponge Rhabdastrella globostellata was able to cope with extreme acidification and deoxygenation seawater. Photosynthetic activity of sponge symbionts was negatively affected during extreme environmental conditions. The sponge loop pathway was disrupted during low tide, which correlated with extreme acidification, deoxygenation and warming seawater.